Conformational equilibrium in supramolecular chemistry: Dibutyltriuret case - Mroczyńska, Karina; Kaczorowska, Małgorzata; Kolehmainen, Erkki; Grubecki, Ireneusz; Pietrzak, Marek; Ośmiałowski, Borys (Beilstein Journal of Organic Chemistry, 2015)
The association of substituted benzoates and naphthyridine dianions was used to study the complexation of dibutyltriuret. The title molecule is the simplest molecule able to form two intramolecular hydrogen bonds. The naphthyridine salt was used to break two intramolecular hydrogen bonds at a time while with the use of substituted benzoates the systematic approach to study association was achieved. Both, titrations and variable temperature measurements shed the light on the importance of conformational equilibrium and its influence on association in solution. Moreover, the associates were observed by mass spectrometry. The DFT-based computations for complexes and single bond rotational barriers supports experimental data and helps understanding the properties of multiply hydrogen bonded complexes.
Keywords: association; hydrogen bonding; NMR; rotamerism; supramolecular chemistry